2012
DOI: 10.1128/jcm.05253-11
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Genotyping of Cytomegalovirus in Dried Blood Spots by Multiplex Real-Time PCR Assays Targeting the Envelope Glycoprotein gB and gH Genes

Abstract: Genotyping of cytomegalovirus (CMV) is useful to examine potential differences in the pathogenicity of strains and to demonstrate coinfection with multiple strains involved in CMV disease in adults and congenitally infected newborns. Studies on genotyping of CMV in dried blood spots (DBS) are rare and have been hampered by the small amount of dried blood available. In this study, two multiplex real-time PCR assays for rapid gB and gH genotyping of CMV in DBS were developed. Validation of the assays with 39 CMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 44 publications
(66 reference statements)
3
29
0
4
Order By: Relevance
“…Furthermore, despite genotypic variability of CMV seems to be geographically related, different genotypification methodologies have proven different sensitivities for mixed infection detection. 26,27 Mixed infection with multiple CMV strains occurs in various patient populations, including immunocompetent and immunocompromised subjects. However, infection with multiple strains has rarely been described in NB with congenital CMV.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite genotypic variability of CMV seems to be geographically related, different genotypification methodologies have proven different sensitivities for mixed infection detection. 26,27 Mixed infection with multiple CMV strains occurs in various patient populations, including immunocompetent and immunocompromised subjects. However, infection with multiple strains has rarely been described in NB with congenital CMV.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies directed towards assessing the impact of genotype features on disease have yielded conflicting results. Nevertheless, it appears that in certain circumstances strain type may have a role in the occurrence of CMV disease; for instance, most studies in HIV-positive patients report gB2 as the most common genotype [4,6,15,16,28,29,30,31,32,33], while in transplant patients gB1 is the predominant genotype [5,15,16,17,18,19,20,21,22,23,24,25,26,27]. Also, the interpretation of these results is affected by the frequent detection of coinfections with two or more CMV strains in immunosuppressed patients [22,33].…”
Section: Discussionmentioning
confidence: 99%
“…Among viral factors, genetic variability has been analyzed in order to determine the possible association between viral genetic features and infection outcome; several genes have been targeted for evaluation including those encoding for gB, glycoprotein N, glycoprotein O, and the UL144 gene, among others [6,11,12,13,14]. The gB gene has been studied in different risk groups, including both solid organ and hemopoietic transplant patients [5,15,16,17,18,19,20,21,22,23,24,25,26,27], HIV-infected patients [4,6,15,16,28,29,30,31,32,33], infants with congenital infection [3] and healthy subjects [34]. So far, studies directed towards assessing the impact of genotype features on disease have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…A Dutch study performed in adults and infants reported the occurrence of double and triple mixed infections composed of various gB genotypes [29]. …”
Section: Discussionmentioning
confidence: 99%